Use of ICDAS-II, Fluorescence-Based Methods, and Radiography in Detection and Treatment Decision of Occlusal Caries Lesions: An In Vitro Study - Anahita Jablonski-Momeni; Jasmin Stucke; Torben Steinberg; Monika Heinzel-Gutenbrunner (International Journal of Dentistry)
Aim. To use visual inspection (ICDAS-II), laser fluorescence (LF), fluorescence based camera (FC) and radiographic examination (BW) for detection of caries and for treatment decision. Methods. The occlusal sites of 84 extracted permanent teeth were examined using all methods and treatment decisions (preventive or operative care) were recorded based on each method independently. For validation of the findings, fissures were opened with rotating instruments and clinical depth was determined as gold standard. Correlations (𝑟𝑠), sensitivity, specificity and AUC were calculated. McNemar test was used to show whether different methods led to significant changes in treatment decisions. Results. Highest correlation was found between ICDAS-II and FC (𝑟𝑠 0.84), ICDAS-II and gold standard (0.82) and FC and gold standard (0.81). ICDAS-II provided the highest performance (AUC 1.0), followed by FC (0.95) and LF (0.88). The greatest difference was found for treatment planning of dentine lesions, where the use of FC (cut-offs according to the literature) had the greatest agreement between operative treatment and dentine lesions, followed by use of ICDAS-II. Conclusion. ICDAS-II may have high potential for detection and treatment planning, and other devices, especially the fluorescence camera, can add substantial information to the visual examination, enabling examiners plan treatment more accurately.